The bear, the piano, the dog, and the fiddle - Litchfield, David (Boston ; New York : Clarion Books, Houghton Mifflin Harcourt, 2019)
Hugo the dog becomes the star of an all-animal band after learning to play his best friend Hector's fiddle, and despite Hector's jealousy, remains grateful to the man who gave him his start.
Originally published: London : Frances Lincoln Children's Books, 2018.
Keywords: Musicians -- Fiction; Friendship -- Fiction; Dogs -- Fiction; Animals -- Fiction; Bands (Music) -- Fiction; Jealousy -- Fiction; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / Performing Arts / Music; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Animals / Bears; JUVENILE FICTION / Imagination & Play